VIRAL TOURISM DAN TRANSFORMASI ATRAKSI WISATA PURA LEMPUYANG MADYA DI BALI PADA ERA MEDIA SOSIAL - Nyoman Surya Wijaya; Made Darsana; A.A. Ayu Arun Swi Arianti; I Gusti Ayu Eka Suwintari (Jurnal Manajemen Perhotelan dan Pariwisata, 2026)
The phenomenon of viral tourism driven by social media has transformed how tourists perceive and experience destinations, including cultural-spiritual attractions. This study aims to analyze the construction of the tourist gaze, the transformation of destination meanings, and their implications for destination management at Pura Lempuyang Madya, Bali. A qualitative case study approach was employed through digital content analysis and document review of social media posts, tourist reviews, and supporting documents. The findings reveal that social media constructs a visually oriented tourist gaze, reflected in the dominance of photographic activities centered on the iconic Gate of Heaven. This phenomenon has transformed the destination from a cultural-spiritual space into an object of digital visual consumption, while simultaneously encouraging cultural commodification and creating new management challenges. The novelty of this study lies in integrating viral tourism, tourist gaze, destination meaning transformation, cultural commodification, and sustainable destination management within a single analytical framework.